Pengelolaan Adiksi Game Online Dalam Pembelajaran Ketrampilan Komputer Dan Pengelolaan Informasi Pada Siswa SMK Muhammadiyah 6 Gemolong - Hidayah, Nurul; , Prof. Dr. Sutama, M.Pd; , Dr. Sabar Narimo,MM.,M.Pd (2017)
MANAGEMENT OF ONLINE GAME ADDICTION ON LEARNING KKPI AT SMK MUHAMMADIYAH 6 GEMOLONG Nurul Hidayah.Q100150042 ABSTRACT This research aims to: (1) to describe the online game addiction management planning in KKPI learning at SMK Muhammadiyah 6 Gemolong, (2) to describe the implementation of online game addiction management in KKPI learning at SMK Muhammadiyah 6 Gemolong, (3) to describe evaluation from the online game addiction management at SMK Muhammadiyah 6 Gemolong. The research was conducted with a kind of qualitative research with ethnographic approach design. This research collect the data with interviews, documentation and observation. Data analysis use an interactive analysis model. The results of this study are; (1) online game addiction management planning with identification of learners, searching for appropriate learning game reference, making lesson plans and evaluation instruments; (2) implementation of online game addiction in learning KKPI in accordance with the planning that has been made and implemented to adjust the current situation; and (3) evaluation of online game addiction in KKPI learning done during daily test, mid semester test and final semester test. Keywords :management, online game addiction, KKPI learning